Short-term pelvic fracture outcomes in adolescents differ from children and adults in the National Trauma Data Bank. (February 2015) - Marmor, Meir; Elson, Joshua; Mikhail, Christopher; Morshed, Saam; Matityahu, Amir
Background: Pediatric pelvic fractures are associated with high-energy trauma and injury to other systems, leading to an increased incidence of complication and mortality. Previous studies analyzed the pediatric population as a whole, including both children and adolescents. The purpose of this study was to examine whether adolescents with pelvic fracture have different complication and mortality rates compared to younger children and adults. Methods: Using the National Trauma Data Bank, 37, 784 patients below the age of 55 years with pelvic fractures were identified and divided into children (age <13 years), adolescents (age 13–17 years), and adults (age >17 years). Descriptive statistics and bivariate and multivariate analyses were performed. Results: Children had an increased odds of death [odds ratio (OR) 2.29, 95 % confidence interval (CI) 1.96–2.67] and complications (OR 1.36, 95 % CI 1.20–1.55), whereas adolescents had a decrease in odds of death (OR 0.89, 95 % CI 0.74–1.06) and complications (OR 0.70, 95 % CI 0.61–0.81) compared to the adult population. Conclusions: Adolescents with pelvic fractures exhibit a different physiologic response to the children and adult populations. This emphasizes the need to distinguish these subpopulations in future epidemiological research and treatment planning.